Geometric modeling of the unfolding of a rod structure in the form of a double spherical pendulum in weightlessness - Kutsenko, Leonid; Semkiv, Oleg; Asotskyi, Vitalii; Zapolskiy, Leonid; Shoman, Olga; Ismailova, Nelli; Danylenko, Volodymyr; Vinogradov, Stanislav; Sivak, Elizaveta (Eastern-European Journal of Enterprise Technologies, 2018)
We investigated the geometric model of the new technique for unfolding a rod structure, similar to the double spherical pendulum, in weightlessness. Displacements of elements occur due to the pulses from pyrotechnic jet engines acting on the endpoints of links. The motion of the obtained inertial unfolding of a rod structure was described using a Lagrange equation of the second kind. Given the conditions of weightlessness, it was built applying only the kinetic energy of the system. The relevance of the chosen subject is emphasized by the need to choose and study the process of activation of the unfolding of a spatial rod structure. The proposed possible drivers are the pulse pyrotechnic jet engines installed at endpoints of the structure’s links. They are lighter and cheaper compared, for example, to electric motors or spring devices. In addition, they are more efficient economically when the process of unfolding a structure in orbit is planned to be performed only once. We propose a technique for determining the parameters and initial conditions for initiating the oscillations of a double rod structure in order to obtain a cyclic trajectory of the endpoint of the second link. That makes it possible to avoid, when calculating the process of transformation, the chaotic movements of the structure’s elements. We built the time-dependent charts of change in the functions of generalized coordinates, as well as the first and second derivatives from these functions. Therefore, there is a possibility to estimate the force characteristics of the system at the moment of braking (locking) the process of unfolding. The results are intended for the geometric modeling of one of the variants for unfolding the large-sized structures under conditions of weightlessness, for example, force frames for solar mirrors or space antennas, as well as other large-scale orbital infrastructures.